Twice-Exceptionality (2e): A Perspective of Pre-service and In-service Special Educators - Pahwa, Tanvi; Alam, Mohd Noor; Khan, Aerum; Khan, Mohd Faijullah (Voices of Teachers and Teacher Educators, 2026)
This research aims to study the awareness of pre-service and in-service special educators about twice-exceptionality and characteristics of twice-exceptional (2e) learners in the National Capital Region of Delhi (Delhi NCR). Twice-exceptional learners are characterized by the coexistence of high intellectual abilities and specific learning challenges or disabilities, or any other developmental disability making a unique set of needs that demand specialized attention in educational settings for the learner. This study employs a comprehensive survey method, engaging a diverse sample of 132 in-service and pre-service special educators teaching in inclusive schools across Delhi NCR. The pre-service teachers are the teacher trainees of B.Ed. and M.Ed. Special Education programmes doing their teaching practice under the supervision of the school teachers and supervisors from their institutes. This was done to explore the awareness levels among them about the twice-exceptional learners in their schools, the teaching practices for twice-exceptional learners that are followed, and to explore the existing gaps and requirements for professional development of special educators to work with individuals with twice-exceptionality. The findings of the study help to understand the existing learning gaps in the awareness levels of educators working in inclusive schools of Delhi NCR, the addressing of hindrances in the optimal support to twiceexceptional learners to begin with addressing their duality and dual uniqueness nature of learning and gifted skills. Furthermore, this study explores the influence of various factors which may affect the understanding of the specific needs of twice-exceptional learners in classrooms, such as teaching experience, educational background of the educators, educators’ awareness levels about disabilities and giftedness, and deep understanding of multiple exceptionalities that might exist in an individual and the process of finding suitable solutions to the child and the parents to cushion the learning support for the individual. The implications of this study suggest that there is an opportunity gap, educational gap , training gap and lack of resources for diverse learning needs that has led to broaden the gap in understanding dual exceptionalities and, moreover, there is no evidence of any suggested practices or educational plan to be followed or to teach such learners in the near future. Finding of the study reveals that 70% of special educators are aware of the term ‘ twiceexceptionality,’ however, only 53% of special educators are aware of the traits of twiceexceptional learners. The study also found that Individualized Education Plans (IEPs) are the most widely used strategy, with 80% of educators relying on it followed by differentiated instructions and assignments used by 58% of educators to cater to the learning needs of twice-exceptional learners. The findings of this research reflect that most of the educators believe that there is an urgent need to learn about the concept of twice-exceptionality to develop new strategies which are suitable for the dual nature of such learners to address their gifted skills as well as learning challenges.